Clinical relevance, etiology and imaging Characteristics of cerebral venous sinus Thrombosis at a tertiary care hospital in Bangladesh - Islam, Md Rashedul; Rahman, Aminur; Rahman, Tanbin; Hossen Khan, Mohammad Sakhawat; Alam, Dilruba; Habib, Rumana (Bangladesh Journal of Medicine, 2023)
Background: Cerebral sinus thrombus (CVST) is a rare form of stroke often affects young people with diverse clinical, etiological and radiological presentation. The aim of the study was to evaluate clinical relevance, etiologies, and imaging characteristics of CVST in Bangladesh. Methods: A prospective, observational study was done at a tertiary care hospital with patients recruited in the period of January 2021 to January 2023. 38 patients with clinical and radiological features suggestive of cerebral venous sinus thrombosis (CVST) were studied with thorough clinical evaluation and comprehensive work up. Results: The mean age of presentation was 28.42 years with female predominance (n = 24). Headache was the most common presenting symptoms (92%, n = 35) followed by vomiting (52%, n = 20). Hemi paresis (38%; n = 14) was the most common clinical sign followed by cranial nerve palsy (26%, n = 10). 31% of the patients (n=12) had provoked CVST among those the most common cause was found to be pregnancy/puerperium in 58% (n = 7 patients) followed by OCP which were 25% (n = 3). 69 % of the patients (n=26) had unprovoked CVST among those the most common cause was found to be prothrombotic conditions in 85% (n = 22 patients) followed by idiopathic which were 15% (n = 4). In magnetic resonance imaging venography (MRV), 74% of patients (n = 28) had thrombosis of transverse sinus, 53% of patients (n = 20) had thrombosis of the sigmoid sinus and 42% patients (n = 16) of patients had saggital sinus thrombosis. Conclusion: Clinical presentation is variable, etiology must be determined, and diagnostic method of choice is MRV. Headache was most the common clinical presentation and the most common etiological factor is puerperium. Provoked CVST is more common than unprovoked CVST and transverse sinus thrombosis frequently involved. Bangladesh J Medicine 2023; 34(3): 186-191